Quid pro quo: friendly information exchange between rivals - Andreas Blume; In-Uck Park (Theoretical Economics, 2022)
We show that information exchange via disclosure is possible in equilibrium even when it is certain that whenever one party learns the truth, the other loses. The incentive to disclose results either from an expectation of disclosure being reciprocated – the quid pro quo motive – or from the possibility of learning from the rival's failure to act in response to a disclosure – the screening motive. Alternating and gradual disclosures are generally indispensable for information exchange and the number of disclosure rounds grows without bound if the agents' initial information becomes sufficiently diffuse – in that sense, the less informed agents are the more they talk. Patient individuals can achieve efficiency by means of continuous alternating disclosures of limited amounts of information. This provides a rationale for protracted dialogues.
Keywords: C72; C73; D82; D83; 330; Alternating information disclosure; dynamic communication; two-sided incomplete information